Objective-C programming fundamentals and advenced - DeVoe, Jiva (LiveLessons (Indianapolis, Ind.), 2012)
"In the Fundamentals section Jiva Devoe helps the viewer understand the key concepts and fundamentals of the Objective-C language. This video covers basic objective-c syntax, objects, memory management, protocols, the foundation framework and errors. The newest features in Objective-C such as ARC, blocks, and properties are included. After watching this video, viewers should be able to build and run basic Objective-c programs. In the Advanced section viewers will learn how to use blocks, use categories to extend the capabilities of existing classes, use keyvalue coding and keyvalue observing, use threading to harness the power of multiprocessor and multicore machines, understand design patterns e commonly used in Objective-C, and how to serialize and deserialize objects to property lists and to JSON strings. Finally, the video covers best practices for programming clean code in Objective-C. When viewers have completed these lessons, they will have an understanding of the necessary aspects of Objective-C that are needed to begin writing applications using cocoa and cocoa touch."--Resource description page.